Ive tried looking for a similar question on the forums but I couldnt find any. I would greatly appreciate any help given! enter image description here

  • 1
    $\begingroup$ You can use the chain rule to better define $f'(x)$ and $w'(x)$ $\endgroup$ – WaveX Dec 8 '16 at 16:46

There is something called chain rule. In your case $f(x)=g(h(x))$. So $f'(x)=g'(h(x))\cdot h'(x)$.

Therefore $f'(3)=g'(h(1))h'(1)=g(3)\times (-0.5)=2\times(-0.5)=-1$. Do the other one yourself.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.